Triclosan Promotes Staphylococcus aureus Nasal Colonization - Adnan K. Syed (American Society for Microbiology, 2014)
ABSTRACT The biocide triclosan is used in many personal care products, including toothpastes, soaps, clothing, and medical equipment. Consequently, it is present as a contaminant in the environment and has been detected in some human fluids, including serum, urine, and milk. Staphylococcus aureus is an opportunistic pathogen that colonizes the noses and throats of approximately 30% of the population. Colonization with S. aureus is known to be a risk factor for several types of infection. Here we demonstrate that triclosan is commonly found in the nasal secretions of healthy adults and the presence of triclosan trends positively with nasal colonization by S. aureus. We demonstrate that triclosan can promote the binding of S. aureus to host proteins such as collagen, fibronectin, and keratin, as well as inanimate surfaces such as plastic and glass. Lastly, triclosan-exposed rats are more susceptible to nasal colonization with S. aureus. These data reveal a novel factor that influences the ability of S. aureus to bind surfaces and alters S. aureus nasal colonization. IMPORTANCE Triclosan has been used as a biocide for over 40 years, but the broader effects that it has on the human microbiome have not been investigated. We demonstrate that triclosan is present in nasal secretions of a large portion of a test population and its presence correlates with Staphylococcus aureus nasal colonization. Triclosan also promotes the binding of S. aureus to human proteins and increases the susceptibility of rats to nasal colonization by S. aureus. These findings are significant because S. aureus colonization is a known risk factor for the development of several types of infections. Our data demonstrate the unintended consequences of unregulated triclosan use and contribute to the growing body of research demonstrating inadvertent effects of triclosan on the environment and human health.